Elucidation of Novel cis-Regulatory Elements and Promoter Structures Involved in Iron Excess Response Mechanisms in Rice Using a Bioinformatics Approach - Kakei, Yusuke; Masuda, Hiroshi; Nishizawa, Naoko K.; Hattori, Hiroyuki; Aung, May Sann (Frontiers in Plant Science, 2021)
Iron (Fe) excess is a major constraint on crop production in flooded acidic soils, particularly in rice cultivation. Fe excess in plants activates a complex mechanism and network regulating Fe exclusion by roots and isolation in various tissues. In rice, the transcription factors and cis-regulatory elements (CREs) that regulate Fe-excess response mechanisms remain largely elusive. We previously reported comprehensive microarray analyses of several rice tissues in response to various levels of Fe-excess stress. In this study, we further explored novel CREs and promoter sequences in rice using bioinformatics approaches with this microarray data. We first performed network analyses to predict Fe excess related CREs through the categorization of the gene expression patterns of Fe-excess-responsive transcriptional regulons, and found four major expression types, including Fe storage, Fe chelator, Fe uptake, and WRKY and other co-expression types. Next, we explored CREs within these four clusters of gene expression types using a machine-learning method called microarray-associated motif analyzer (MAMA), which we previously established. Based on the presence or absence of new candidate CREs and known CREs, we found that the Boruta-XGBoost model using MAMA CREs and PLACE CREs explained expression patterns with high accuracy of about 82%. Expression patterns were explained based on enriched sequences of both known and novel CREs. We searched for several novel cis-elements as candidate Fe-excess CREs including CGACACGC and CATCACAC motifs. We further investigated new roles of known CREs in the Fe-excess response, including the FAM1 motif, IDEF1-, bZIP-, WRKY-, bHLH-, MADS-box-, TBP- and E2F- binding sequence-containing motifs among Fe-excess-responsive genes. Through a comprehensive bioinformatics approach, we identified 350 conserved sequences of CREs directly related to the Fe excess response in various rice tissues. In addition, we revealed a molecular mechanism regulating Fe-excess-responsive genes based on CREs. Together, our findings about CREs and conserved sequences will provide a comprehensive resource for discovery of genes and transcription factors involved in Fe-excess-responsive pathways, clarification of the Fe-excess response mechanism in rice, and application of the promoter sequences to produce genotypes tolerant of Fe excess.